Integrasi Green Procurement Dalam Kontrak Pengadaan: Strategi Mewujudkan Pengadaan Berkelanjutan yang Berdampak di Indonesia - Mustika Putra Rokan; Muhammad Natsir; M. Iqbal Asnawi; M. Irfan Islami Rambe; Vita Cita Emia Tarigan (Jurnal Hukum Lex Generalis, 2025)
Green Procurement constitutes a strategic policy to support sustainable development; however, in practice, its implementation in Indonesia remains largely confined to the tendering stage. In fact, procurement contracts serve as a legal instrument that ensures sustainability is genuinely realized. This article examines the integration of green principles into contracts through performance clauses, life-cycle costing, incentive mechanisms, and enforceable sanctions. The study identifies existing regulatory gaps and weak implementation, while at the same time proposing a contractual framework that is more operational, measurable, and capable of generating tangible impacts on the environment, the economy, and society.